Desarrollo de contenidos dinámicos mediante el uso de exelearning para los estudiantes del décimo año de la Escuela Miguel Heredia Crespo - Malla Navarro, Edisson Fernando (Machala, Universidad Técnica de Machala, 2022)
The present research project was developed in the Mixed Fiscal School "Miguel Heredia Crespo" located in the province of Azuay of the Canton Camilo Ponce Enríquez directed for the students of the parallel tenth grade "A" in the subject of Social Studies of the school year 2021- 2022 jointly with María Rueda, teacher of the same. It is important to take into consideration the inclusion of students within the spaces of interaction through Information and Communication Technologies (ICT), which allowed an improvement in today's society due to the development of technological tools focused on the educational field. . Through conducting the research, it has as a priority to strengthen the educational process through interactive content on the eXe Learning platform in order to improve cognitive abilities in the subject of Social Studies. Through this, it will allow interactivity and development of activities facilitating teaching practice according to the object of study, it also includes interactive videos that will strengthen teaching to the student and playful games as a mediator of learning that the student acquired in the educational process. . The eXe Learning interactive platform allows the user to explore various contents for the fulfillment of various activities in order to facilitate the use and incorporation of video such as interactivity, carrying out evaluations for work with other free software such as GeoGebra, making rubrics academic and facilitate the creation of mental maps, generator of avatars for the development of new content. Through the investigative process, the Kanban methodology was used; it is one of the ways where the interactive platform will be in the environment where, therefore, it allowed directing the communication and the development of different tasks to achieve meaningful learning, so that the author concludes with his ideas. to project it in the present project. Towards the research methodology, the Mixed approach was used, which allowed a greater theoretical-practical, quantitative approach; managing to reach values, quantities within the graphs and statistical tables, qualitative; through data collection, analysis and interpretation of information allowing the development of research to achieve a feasible result. After the exploration of information and data, the eXe Learning interactive platform was taken into consideration for the development of dynamic content, interaction, exploration and development of activities so that the student relates to the interactive platform and thus the teacher strengthens his educational practice. for use within the classroom process. In short, to the interface and analysis of the interactive platform, the result has been achieved within the incorporation of the prototype in the classroom. The students were able to show and carry out its operation as well as their interest in participating in classes, thus facilitating their cognitive abilities, it is to be considered that the prototype is fundamental for the development of activities and interaction in the classroom above all, it is necessary that other teachers apply this platform to improve the teaching-learning process.
La presente investigación se desarrolló en la Escuela Fiscal Mixta “Miguel Heredia Crespo” ubicado en el Cantón Camilo Ponce Enríquez, perteneciente a la provincia del Azuay del Ecuador dirigido para los estudiantes del décimo grado paralelo “A” en la asignatura de Estudios Sociales del año lectivo 2021-2022 conjuntamente con la Licenciada María Rueda docente de la misma. Es importante tomar en consideración la inclusión de los estudiantes dentro de los espacios de interacción por medio de las Tecnologías de información y comunicación (TIC) los mismos que permitieron una mejora en la sociedad actual por el desarrollo de herramientas tecnológicas enfocado en el ámbito educativo. Por medio de la realización de la investigación tiene como prioridad fortalecer el proceso educativo a través de contenidos interactivos en la plataforma eXe Learning con el fin de mejorar las capacidades cognitivas en la asignatura de Estudios Sociales. Por medio de este permitirá la interactividad y desarrollo de actividades facilitando a la práctica docente en función al objeto de estudio, además incluye videos interactivos que va fortalecer la enseñanza al estudiante y los juegos lúdicos como mediador de aprendizaje que el estudiante adquirió en el proceso educativo. La plataforma interactiva eXe Learning permite al usuario explorar contenidos diversos para el cumplimiento de diversas actividades con la finalidad de facilitar el uso y la incorporación de video como la interactividad, la realización de evaluaciones para el trabajo con otro software libre como GeoGebra, realización de rúbricas académicas y facilitar la creación de mapas mentales, generador de avatares para el desarrollo de nuevos contenidos. Mediante el proceso investigativo se utilizó la metodología Kanban es una de las formas donde la plataforma interactiva estará en el entorno donde por ende, permitió dirigir la comunicación y el desarrollo de diferentes tareas para alcanzar el aprendizaje significativo alcance para que el autor concluya con sus ideas para proyectarlo en el presente proyecto. Hacia la metodología de investigación se utilizó el enfoque Mixto que permitió un mayor enfoque teórico-práctico, cuantitativo; logrando alcanzar valores, cantidades dentro de las gráficas y tablas estadísticas, cualitativo; por medio de la recolección de datos, análisis e interpretación de información permitiendo el desarrollo de la investigación para lograr un resultado factible. Luego de la exploración de información y datos se tomó en consideración la plataforma interactiva eXe Learning para el desarrollo de contenidos dinámicos, interacción, exploración y desarrollo de actividades para que el estudiante se relacione con la plataforma interactiva y así vez el docente fortalezca su práctica educativa para el uso dentro del proceso áulico. En definitiva al interfaz y análisis de la plataforma interactiva, se ha logrado el resultado dentro de la incorporación del prototipo en el aula. Los estudiantes pudieron evidenciar y efectuar su funcionamiento como también su interés por participar dentro de clases así que facilita a sus capacidades cognitivas, es de considerar que el prototipo es fundamental para el desarrollo de actividades y la interacción en el aula sobre todo, es necesario que demás docentes apliquen esta plataforma para mejorar el proceso de enseñanza-aprendizaje.
Keywords: PLATAFORMA INTERACTIVA; ENSEÑANZA; APRENDIZAJE; PROTOTIPO